Crop insurance policies in India: An empirical analysis of Pradhan Mantri Fasal Bima Yojana - Sandeep Kaur; Hem Raj; Harpreet Singh; Vijay Kumar Chattu (Risks, 2021)
India is home to over one-third of all undernourished children worldwide, and it ranks 94th out of 107 nations in the Global Hunger Index 2020. Instability in production and market risks make agriculture a risky business and directly affect farmers' income levels, thereby impacting food security. This review aimed to understand various features of different crop insurance policies in India and to analyze the Pradhan Mantri Fasal Bima Yojana's (PMFBY) impacts on Indian farmers. A literature search was performed in all popular databases, including Scopus, Web of Science, ProQuest, AGRICOLA, AGRIS, and Google search engines, as well as annual Indian government reports. The keywords "Crop Insurance" OR "Pradhan Mantri Fasal Bima Yojana" OR "National Agriculture Schemes" AND "India" were searched to obtain relevant articles. By using cumulative data, we conducted a multiple regression analysis and a model was developed to estimate the effects of insurance characteristics on farmer coverage for the years 2017-2018 and 2018-2019. Agricultural insurance coverage under PMFBY remained low in terms of the number of farmers insured, the area insured, claims paid, and total farmers benefited. Compared to other schemes, the beneficiary and claim premium ratios were substantially lower under the PMFBY. The multiple regression analysis showed that farmers' premiums have a significant effect on the number of farmers insured over time, although the subsidies do not have a significant influence in farmers' insurance participation. Delays in claim settlement, the complexity of the system, and a lack of awareness among farmers are the major weaknesses of the PMFBY. Greater use of digital media could help spread awareness of these schemes among farmers.
Keywords: 330; crop insurance; food security; financing schemes; India; Pradhan Mantri Fasal Bima Yojana